Soil physical characteristics and corn grain yield as a function of cover crops (Research, Society and Development, 2022)
The knowledge of the physical properties of the soil and the potential of the cultures called “restoratives” of structure is important for decision making about agricultural management, thus, the study involving cover crops are important when aiming at the sustainability of the crops. Thus, this study aimed to evaluate the impact of cover crops on the structure of a clayey Oxisol under no-tillage system and its effects on corn grain yield. The treatments consisted of six winter cover species: white oats, black oats, rye, black oats + radish, black oats + white lupine, black oats + peas, in addition to the traditional no-tillage system (control). The experimental design was completely randomized with 4 replications in experimental plots of 20x16 m. Undisturbed soil samples were collected in layers of 0.00-0.10 m, 0.1-0.20 m and 0.20-0.30 m, after desiccation of the cover species and after corn harvesting, on the which the corn crop was implemented. Corn grain yield was evaluated with 3 replications, in an area of ​​13.5 m², and grain moisture was corrected to 13%. Treatment means were compared using the Tukey test at 5% significance, using the Sisvar program. The cover crops that showed greater efficiency in soil restructuring were the intercropping black oat + white lupine and black oat + forage pea. As for corn grain yield, white oat was the treatment that provided the highest corn grain yield, not differing from rye, black oat + turnip, black oat + white lupine and the traditional no-tillage system, showing good results. soil conditions and climate of the experimental area.